Applicability evaluation of deep eutectic solvents–cellulase system for lignocellulose hydrolysis - Gunny, Ahmad Anas Nagoor; Arbain, Dachyar; Nashef, Enas Muen; Jamal, Parveen (Elsevier, 2015)
Deep Eutectic Solvents (DESs) have recently emerged as a new generation of ionic liquids for lignocellulose pretreatment. However, DESs contain salt components which tend to inactivate cellulase in the subsequent saccharification process. To alleviate this problem, it is necessary to evaluate the applicability of the DESs–Cellulase system. This was accomplished in the present study by first studying the stability of cellulase in the presence of selected DESs followed by applicability evaluation based on glucose production, energy consumption and kinetic performance. Results showed that the cellulase was able to retain more than 90% of its original activity in the presence of 10% (v/v) for glycerol based DES (GLY) and ethylene glycol based DES (EG). Furthermore, both DESs system exhibited higher glucose percentage enhancement and lower energy consumption as compared to diluted alkali system. Among the two DESs studied, EG showed comparatively better kinetic performance.